Interferon system in acute transient synovitis. Issue 10 (October 1985) - Leibowitz, E; Levin, S; Torten, J; Meyer, R
Abstract : The interferon system of 20 children aged 2 to 11 years (mean 5 years), diagnosed as having transient synovitis of the hip by clinical criteria, was studied. The mean blood interferon concentration was significantly higher than that of normal children, and the incidence of an antiviral state of cells (in 78% of patients) was also significantly higher than in the control group. These findings are compatible with the hypothesis that the aetiology of transient synovitis is an acute, possibly unusual, viral infection.